Wentworth. Season 1 [videorecording (DVD)] - Cormack, Danielle; Da Silva, Nicole; McQuade, Kris, 1952-; Walsman, Leeanna, 1979- (Acorn, 2016)
When Bea Smith arrives at Wentworth Prison, arrested for the attempted murder of her abusive husband, she is thrown head-first into a hostile and unforgiving environment with rules of its own. Bea tries to stay out of trouble, but quickly becomes caught up in a brutal rivalry between celebrity inmate Franky and former mob boss Jacs. Wentworth proves to be a dangerous place for the officers as well as the inmates, who are often prisoners to their own personal dilemmas.